2016
DOI: 10.7161/omuanajas.260980
|View full text |Cite
|
Sign up to set email alerts
|

Determining the residue and energy potential of field crops in Çanakkale

Abstract: ÖZET Çanakkale'de tarım sektörü, oldukça geniş ürün çeşitliliğine sahiptir. Tarımsal faaliyetler arasında tarla tarımı, toplam tarım alanının %67'sinde yürütülmektedir. Bu alanlarda, artık potansiyeli bulunan ürünlerin yaygın olarak yetiştirilmekte olması nedeniyle, Çanakkale'de dikkate değer miktarlarda tarımsal artıklar oluşmaktadır. Söz konusu artıklar, Çanakkale için olduğu kadar Türkiye için de enerji kaynağı olarak önemli biyokütle potansiyeli oluşturmaktadır. Bu çalışmada, Çanakkale ilinin tarla tarımı … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…The fruit-bearing trees almond, apple, apricot, cherry, peach, pear, plum, and sour cherry trees, which are grown in almost all provinces in Turkey and pruned every 1 to 2 years, were taken into consideration (Ministry of Agriculture and Forestry 2022). Bilandzija et al (2012) and Sumer et al (2016) reported the pruning coefficients of the almond, apple, apricot, cherry, peach, pear, plum, and sour cherry trees as 5. 81, 2.34, 5.79, 5.90, 7.23, 2.45, 7.34, and 5.37 kg/tree year, respectively.…”
Section: Calculation Of the Biochar Production Potential Of Pruning W...mentioning
confidence: 99%
See 4 more Smart Citations
“…The fruit-bearing trees almond, apple, apricot, cherry, peach, pear, plum, and sour cherry trees, which are grown in almost all provinces in Turkey and pruned every 1 to 2 years, were taken into consideration (Ministry of Agriculture and Forestry 2022). Bilandzija et al (2012) and Sumer et al (2016) reported the pruning coefficients of the almond, apple, apricot, cherry, peach, pear, plum, and sour cherry trees as 5. 81, 2.34, 5.79, 5.90, 7.23, 2.45, 7.34, and 5.37 kg/tree year, respectively.…”
Section: Calculation Of the Biochar Production Potential Of Pruning W...mentioning
confidence: 99%
“…1. The studies conducted by Kaygusuz (2001), Lora andAndrade (2009), andSumer et al (2016) report that 70% of the total biomass can be used for generating energy. Therefore, the biomass usable ratio was admittedly 70%.…”
Section: Calculation Of the Biochar Production Potential Of Pruning W...mentioning
confidence: 99%
See 3 more Smart Citations